2009
DOI: 10.1016/j.otohns.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Persistent pediatric obstructive sleep apnea and lingual tonsillectomy

Abstract: Endoscopic-assisted coblation lingual tonsillectomy is an effective technique for the treatment of lingual tonsillar hypertrophy causing persistent obstructive sleep apnea in some children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 15 publications
2
99
0
1
Order By: Relevance
“…Recently, Lin and Koltai [26] used endoscopic-assisted coblation lingual tonsillectomy for treatment of cases with LTH; although the method was effective in relieving symptoms with no reported post-operative edema, 2 out of 26 cases developed adhesions between tongue base and epiglottis, however this complication did not affect feeding or breathing. In our study, we performed lingual tonsillectomy using unipolar diathermy, 3 out of 16 cases developed post-operative edema.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lin and Koltai [26] used endoscopic-assisted coblation lingual tonsillectomy for treatment of cases with LTH; although the method was effective in relieving symptoms with no reported post-operative edema, 2 out of 26 cases developed adhesions between tongue base and epiglottis, however this complication did not affect feeding or breathing. In our study, we performed lingual tonsillectomy using unipolar diathermy, 3 out of 16 cases developed post-operative edema.…”
Section: Discussionmentioning
confidence: 99%
“…However, post-operative PSG showed persistent apnea in two cases that demonstrated mild apnea after they had moderate apnea pre-operatively; one of them has Down's syndrome and the other has MPS. Many authors commented on factors that may contribute to treatment failure of OSA, such factors may include craniofacial disproportion, hypotonia, and oropharyngeal softtissue redundancy typically associated with obesity and mucopolysaccharidoses [3,12,17,[25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Sleep endoscopy is typically performed immediately before targeted surgery that can be done under the same general anesthetic. 10,11 In cases of lingual tonsil hypertrophy with symptoms of sleep-disordered breathing, a formal polysomnogram would be appropriate to verify the presence and severity of OSA or hypopnea. Continuous positive airway pressure (CPAP) therapy can be effective, and a trial of CPAP can be offered to appropriate patients as an alternative to surgery.…”
Section: Preoperative Evaluationmentioning
confidence: 99%
“…This author prefers use of a 4-mm 701 telescope ( Figure 1) to visualize the operative field endoscopically, though others have described use of a 4-mm 301 telescope. 11 An alternative method of exposing the lingual tonsils would be rigid suspension laryngoscopy, using an operating laryngoscope such as the wide-mouthed Lindholm 15 or the bivalved Weerda 16 laryngoscopes. In either case, the lingual tonsil tissue is visualized with an operating microscope, and instruments are introduced either through the laryngoscope or around it ( Figure 2).…”
Section: Surgical Techniquementioning
confidence: 99%
“…Genioglossal advancement, radiofrequency ablation of the tongue, partial midline glossectomy, lingual tonsillectomy are all surgical options that are aimed at improving oropharyngeal and hypopharyngeal obstruction with varying degrees of reported success. [82][83][84][85][86][87] Rapid maxillary expansion devices have been described in prepubertal children in an effort to widen the hard palate and enlarge the nasal cavity. Villa and colleagues 88,89 reported that, in 14 children, a mean expansion of 3.7 mm for the intercanine distance and 5.0 mm for the interpremolar distance led to an improvement in AHI from 5.8 to 1.5 events per hour, a reduction in snoring, and a reduction in daytime symptoms; this improvement was found to be persistent at 24-month follow-up PSG.…”
Section: Persistent Osasmentioning
confidence: 99%